The Black Sea and the early civilizations of Europe, the Near East and Asia - Ivanova-Bieg, Maria (Cambridge Univ. Press, 2013)
"The Black Sea lies at the junction of three major cultural areas: Europe, Central Asia, and the Near East. It plays a crucial role in enduring discussions about the impact of complex Near Eastern societies on European societies, and the repercussions of early urbanization across Eurasia. This book presents the first comprehensive overview of the Black Sea region in the prehistoric period. It penetrates artificial boundaries imposed by traditions, politics, and language to encompass both the European and Asiatic coasts and both Eastern European and Western scholarly literature. With a critical compilation and synthesis of archaeological data, this study situates the prehistoric Black Sea in a global historical context. By adopting the perspective of technology and innovation, it transcends a purely descriptive account of material culture and emphasizes society, human interaction, and engagement with the material world"--